PERSEPSI PASIEN TERHADAP MUTU PELAYANAN KEPERAWATAN DI INSTALASI RAWAT INAP RUMAH SAKIT TORABELO KABUPATEN SIGI - Andi Nur Indah Sari; Ferdy Fernandi (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2023)
Nursing services are an integral part of hospital health services which have a role in achieving efficiency, the quality of the image of the hospital in society. Nurses are one of the professional staff, so it isnecessary to improve the quality of hospital nursing care services. The results of the interviews conducted by the researchers showed that 10 patients said that the service provided was quite good and satisfactory, but there were 3 patients who said they were not satisfied with the services provided, were not responsive to complaints from patients who were treated in the room. This study aims to determine the patient's perception of the quality of nursing services in the inpatient installation room of the Torabelo Sigi Hospital. This type of research used a descriptive research design method, at the inpatient installation of Tora Belo General Hospital, Sigi Regency. Spruce Room, Ebony. Data collection uses a questionnaire. The variable in this study is the patient's perception of the quality of nursing services. Data analysis using univariate analysis. The population in this study were all hospitalized patients with a total sample of 44 people using proportional sampling by means of accidental sampling that met the inclusion and exclusion criteria. The results of the research on patient perceptions of the quality of nursing services in the inpatient installation room of the Tora Belo Regional General Hospital, Sigi Regency, showed that out of 44 respondents, more patients had a good perception, namely 23 (52.3%), while patients who had a poor perception, namely 21 (47) ,7%). Based on the research results, it can be concluded that the majority of respondents have a good perception of the quality of nursing services at the Tora Belo General Hospital, Sigi Regency. It is hoped that the Tora Belo General Hospital can further improve the quality of nursing and health services through training programs or health seminars.